Public perception of the impact of climate change on the spread of infectious diseases and negative effects of epidemics - Tadić Violeta (University of Belgrade - Faculty of Security Studies, Belgrade, 2020)
The aim of the research was to determine the extent to which citizens perceive the connection between climate change and infectious diseases, i.e. whether they recognize them as a risk factor that contributes to the emergence and distribution of infectious diseases, and to what extent they see epidemics as a serious (security) threat. At the same time, the respondents' familiarity with key concepts was examined. The research was conducted on a convenient sample of 140 respondents, with a Questionnaire constructed for that purpose. Descriptive statistics were used in data processing. By analyzing the obtained results, it was determined that the largest percentage of respondents are familiar with the meaning of the term "infectious diseases", then "climate change", as well as the term "epidemic of greater epidemiological significance". Furthermore, a high level of perception of the connection between climate change and infectious diseases, i.e. recognizing the effects they may have on the occurrence and spread of infectious diseases. According to the obtained results, it was determined that the respondents see the infectious epidemic as a threat to the political stability of the state, health, economic and corporate security, as well as the importance of public education for prevention and response in case of epidemic, but also the lack of adequate capacities and resources for response.